Molecular machines operating on the nanoscale: from classical to quantum - Goychuk, Igor (Beilstein Journal of Nanotechnology, 2016)
The main physical features and operating principles of isothermal nanomachines in the microworld, common to both classical and quantum machines, are reviewed. Special attention is paid to the dual, constructive role of dissipation and thermal fluctuations, the fluctuation–dissipation theorem, heat losses and free energy transduction, thermodynamic efficiency, and thermodynamic efficiency at maximum power. Several basic models are considered and discussed to highlight generic physical features. This work examines some common fallacies that continue to plague the literature. In particular, the erroneous beliefs that one should minimize friction and lower the temperature for high performance of Brownian machines, and that the thermodynamic efficiency at maximum power cannot exceed one-half are discussed. The emerging topic of anomalous molecular motors operating subdiffusively but very efficiently in the viscoelastic environment of living cells is also discussed.
Keywords: anomalous dynamics with memory; Brownian nanomachines; nanoscale friction and thermal noise; quantum effects; thermodynamic efficiency

Cell Biology - Pollard, T. D.; Earnshaw, W. C.; Lippincott-Schwarz, J. (Saunders Elsevier, 2008)

Free Energy Transduction and Biochemical Cycle Kinetics - Hill, T. L. (Springer, 1980)

Biological Physics: Energy, Information, Life - Nelson, P. (W. H. Freeman, 2003)

(untitled) - Kay, E. R.; Leigh, D. A.; Zerbetto, F. (Angew. Chem., Int. Ed., 2006)

(untitled) - Erbas-Cakmak, S.; Leigh, D. A.; McTernan, C. T.; Nussbaumer, A. L. (Chem. Rev., 2015)

(untitled) - Cheng, C.; McGonigal, P. R.; Stoddart, J. F.; Astumian, R. D. (ACS Nano, 2015)

Thermodynamics and an Introduction to Thermostatistics - Callen, H. B. (John Wiley & Sons, 1985)

(untitled) - Curzon, F. L.; Ahlborn, B. (Am. J. Phys., 1975)

(untitled) - Yoshida, M.; Muneyuki, E.; Hisabori, T. (Nat. Rev. Mol. Cell Biol., 2001)

(untitled) - Kubo, R. (Rep. Prog. Theor. Phys., 1966)

(untitled) - Bogolyubov, N. N. (On some Statistical Methods in Mathematical Physics, 1945)
In Russian.

(untitled) - Ford, G. W.; Kac, M.; Mazur, P. (J. Math. Phys., 1965)

(untitled) - Ford, G. W.; Lewis, J. T.; O’Connell, R. F. (Phys. Rev. A, 1988)

(untitled) - Caldeira, A. O.; Leggett, A. J. (Ann. Phys., 1983)

(untitled) - Toyabe, S.; Okamoto, T.; Watanabe-Nakayama, T.; Taketani, H.; Kudo, S.; Muneyuki, E. (Phys. Rev. Lett., 2010)

Quantum Dissipative Systems - Weiss, U. (World Scientific Publishing Co Pte Ltd, 1999)

Quantum Noise: a Handbook of Markovian and Non-Markovian Quantum Stochastic Methods with Applications to Quantum Optics - Gardiner, C. W.; Zoller, P. (Springer, 2000)

(untitled) - Lindblad, G. (Commun. Math. Phys., 1976)

(untitled) - Nakajima, S. (Prog. Theor. Phys., 1958)

(untitled) - Zwanzig, R. (J. Chem. Phys., 1960)

(untitled) - Argyres, P. N.; Kelley, P. L. (Phys. Rev. A, 1966)

(untitled) - Goychuk, I.; Hänggi, P. (Adv. Phys., 2005)

(untitled) - Sekimoto, K. (J. Phys. Soc. Jpn., 1997)

(untitled) - Wyman, J. (Proc. Natl. Acad. Sci. U. S. A., 1975)

(untitled) - Rozenbaum, V. M.; Yang, D.-Y.; Lin, S. H.; Tsong, T. Y. (J. Phys. Chem. B, 2004)

(untitled) - Qian, H. (J. Phys.: Condens. Matter, 2005)

(untitled) - Goychuk, I.; Grifoni, M.; Hänggi, P. (Phys. Rev. Lett., 1998)

(untitled) - Lamoreaux, S. K. (Rep. Prog. Phys., 2005)

(untitled) - Schmiedl, T.; Seifert, U. (EPL, 2008)

(untitled) - Seifert, U. (Phys. Rev. Lett., 2011)

(untitled) - Van den Broeck, C.; Kumar, N.; Lindenberg, K. (Phys. Rev. Lett., 2012)

(untitled) - Golubeva, N.; Imparato, A.; Peliti, L. (EPL, 2012)

(untitled) - Stratonovich, R. L. (Radiotekh. Elektron. (Moscow, Russ. Fed.), 1958)

Topics in the Theory of Random Noise - Stratonovich, R. L. (Gordon and Breah, 1967)

The Fokker-Planck Equation: Methods of Solution and Applications - Risken, H. (Springer, 1989)

(untitled) - Reimann, P. (Phys. Rep., 2002)

(untitled) - Wikström, M. (Biochim. Biophys. Acta, 2004)

Physical Chemistry - Atkins, P.; de Paula, J. (Oxford University Press, 2006)

Chemical Dynamics in Condensed Phases: Relaxation, Transfer and Reactions in Condensed Molecular Systems - Nitzan, A. (Oxford University Press, 2007)

(untitled) - Goychuk, I. A.; Petrov, E. G.; May, V. (Chem. Phys. Lett., 1996)

(untitled) - Goychuk, I. A.; Petrov, E. G.; May, V. (Phys. Rev. E, 1997)

(untitled) - Goychuk, I. A.; Petrov, E. G.; May, V. (J. Chem. Phys., 1997)

(untitled) - Flach, S.; Yevtuschenko, O.; Zolotaryuk, Y. (Phys. Rev. Lett., 2000)

Lecture Notes in Physics: Stochastic Processes in Physics, Chemistry, and Biology - Goychuk, I.; Hänggi, P. (Directed current without dissipation: reincarnation of a Maxwell-Loschmidt demon, 2000)

(untitled) - Wonneberger, W.; Breymayer, H.-J. (Z. Phys. B, 1984)

(untitled) - Goychuk, I.; Hänggi, P. (Europhys. Lett., 1998)

(untitled) - Goychuk, I.; Hänggi, P. (J. Phys. Chem. B, 2001)

(untitled) - Dykman, M. I.; Rabitz, H.; Smelyanskiy, V. N.; Vugmeister, B. E. (Phys. Rev. Lett., 1997)

(untitled) - Gaspard, P. (Physica A, 2006)

(untitled) - Paschotta, R. (Opt. Photonik, 2009)

(untitled) - Astumian, R. D. (Proc. Natl. Acad. Sci. U. S. A., 2007)

(untitled) - Landauer, R. (Physica A, 1999)

(untitled) - Bennet, C. H. (Int. J. Theor. Phys., 1982)

(untitled) - Fredkin, E.; Toffoli, T. (Int. J. Theor. Phys., 1982)

Feynman Lectures on Computation - Feynman, R. (Addison-Wesley, 1996)

(untitled) - Kish, L. B. (Phys. Lett. A, 2002)

(untitled) - Jardetzky, O. (Nature (London), 1966)

(untitled) - Anandan, J.; Christian, J.; Wanelik, K. (Am. J. Phys., 1997)

(untitled) - Sinitsyn, N. A.; Nemenman, I. (EPL, 2007)

(untitled) - Goychuk, I. (Mol. Simul., 2006)

(untitled) - Barkai, E.; Garini, Y.; Metzler, R. (Phys. Today, 2012)

(untitled) - Höfling, F.; Franosch, T. (Rep. Prog. Phys., 2013)

(untitled) - Guigas, G.; Kalla, C.; Weiss, M. (Biophys. J., 2007)

(untitled) - Saxton, M. J.; Jacobson, K. (Annu. Rev. Biophys. Biomol. Struct., 1997)

(untitled) - Seisenberger, G.; Ried, M. U.; Endress, T.; Büning, H.; Hallek, M.; Bräuchle, C. (Science, 2001)

(untitled) - Golding, I.; Cox, E. C. (Phys. Rev. Lett., 2006)

(untitled) - Tolić-Nørrelykke, I. M.; Munteanu, E.-L.; Thon, G.; Oddershede, L.; Berg-Sørensen, K. (Phys. Rev. Lett., 2004)

(untitled) - Jeon, J.-H.; Tejedor, V.; Burov, S.; Barkai, E.; Selhuber-Unkel, C.; Berg-Sørensen, K.; Oddershede, L.; Metzler, R. (Phys. Rev. Lett., 2011)

(untitled) - Parry, B. R.; Surovtsev, I. V.; Cabeen, M. T.; O’Hern, C. S.; Dufresne, E. R.; Jacobs-Wagner, C. (Cell, 2014)

Advances in Chemical Physics - Goychuk, I. (Viscoelastic Subdiffusion: Generalized Langevin Equation Approach, 2012)

(untitled) - Waigh, T. A. (Rep. Prog. Phys., 2005)

(untitled) - Goychuk, I.; Hänggi, P. (Phys. Rev. Lett., 2007)

(untitled) - Goychuk, I. (Phys. Rev. E, 2015)

(untitled) - Goychuk, I. (Phys. Rev. E, 2009)

(untitled) - Siegle, P.; Goychuk, I.; Talkner, P.; Hänggi, P. (Phys. Rev. E, 2010)

(untitled) - Siegle, P.; Goychuk, I.; Hänggi, P. (Phys. Rev. Lett., 2010)

(untitled) - Siegle, P.; Goychuk, I.; Hänggi, P. (EPL, 2011)

(untitled) - Caspi, A.; Granek, R.; Elbaum, M. (Phys. Rev. E, 2002)

(untitled) - Bruno, L.; Levi, V.; Brunstein, M.; Despósito, M. A. (Phys. Rev. E, 2009)

(untitled) - Robert, D.; Nguyen, T.-H.; Gallet, F.; Wilhelm, C. (PLoS One, 2010)

(untitled) - Harrison, A. W.; Kenwright, D. A.; Waigh, T. A.; Woodman, P. G.; Allan, V. J. (Phys. Biol., 2013)

(untitled) - Bruno, L.; Salierno, M.; Wetzler, D. E.; Despósito, M. A.; Levi, V. (PLoS One, 2011)

(untitled) - Goychuk, I.; Kharchenko, V. O.; Metzler, R. (PLoS One, 2014)

(untitled) - Goychuk, I.; Kharchenko, V. O.; Metzler, R. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Goychuk, I. (Phys. Biol., 2015)

(untitled) - Goychuk, I. (Chem. Phys., 2010)

(untitled) - Goychuk, I.; Kharchenko, V. (Phys. Rev. E, 2012)

(untitled) - Kharchenko, V. O.; Goychuk, I. (Phys. Rev. E, 2013)

(untitled) - Goychuk, I.; Kharchenko, V. O. (Math. Modell. Nat. Phenom., 2013)

(untitled) - Kharchenko, V.; Goychuk, I. (New J. Phys., 2012)

(untitled) - Jülicher, F.; Ajdari, A.; Prost, J. (Rev. Mod. Phys., 1997)

(untitled) - Astumian, R. D.; Bier, M. (Biophys. J., 1996)

(untitled) - Parmeggiani, A.; Jülicher, F.; Ajdari, A.; Prost, J. (Phys. Rev. E, 1999)

(untitled) - Herrchen, M.; Öttinger, H. C. (J. Non-Newtonian Fluid Mech., 1997)

(untitled) - Baker, N. A.; Sept, D.; Joseph, S.; Holst, M. J.; McCammon, J. A. (Proc. Natl. Acad. Sci. U. S. A., 2001)

(untitled) - Perez-Carrasco, R.; Sancho, J. M. (Biophys. J., 2010)

(untitled) - Goychuk, I. (Phys. Rev. E, 2012)

(untitled) - Goychuk, I. (Fluct. Noise Lett., 2012)

(untitled) - Goychuk, I.; Kharchenko, V. O. (Phys. Rev. Lett., 2014)